1992
DOI: 10.2118/19433-pa
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated Breaker for Aqueous Polymeric Fluids

Abstract: Conventional breakers reduce fracturing-fluid viscosity much too rapidly, even at moderate temperatures (140 to 200°F), to be used at the high concentrations required to degrade polymers within proppant packs. A delayed-release, encapsulated breaker was developed that permits the use of high breaker concentrations and thus significantly increaSes fracture conductivity. AbstractPersulfates are commonly used as breakers for aqueous fluids viscosified with guar or cellulose derivatives. These breakers are nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…By the reaction of the thickening agent with the cross-linker, the viscosity of the fracturing fluids increases. Breakers of different types such as acids or enzymes or oxidizers are used to reduce the viscosity of the fracturing fluid by cleaving the thickening agent molecules into smaller fragments (Almond and Bland 1984; Gulbis et al 1992; Brannon and Tjon-Joe-Pin 1994; Reinicke et al 2012). The most widely common breakers are oxidizers, as used in the three wells in this study.…”
Section: Laboratory Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the reaction of the thickening agent with the cross-linker, the viscosity of the fracturing fluids increases. Breakers of different types such as acids or enzymes or oxidizers are used to reduce the viscosity of the fracturing fluid by cleaving the thickening agent molecules into smaller fragments (Almond and Bland 1984; Gulbis et al 1992; Brannon and Tjon-Joe-Pin 1994; Reinicke et al 2012). The most widely common breakers are oxidizers, as used in the three wells in this study.…”
Section: Laboratory Analysis Resultsmentioning
confidence: 99%
“…Subsequently, the fracturing fluid must degrade to a very low viscosity to allow flowback and fracture cleanup (Rae and Di Lullo 1996;Lu et al 1999). Any unbroken gel residue remained inside the fracture may cause damage resulting from chemical interactions with time (Almond and Bland 1984; Gulbis et al 1992). Over the past years, hydraulic fracturing in Saudi gas fields underwent significant improvements with regard to job design and execution, fracturing fluid recipes, proppant type and strength, number of fracturing stages, and treatment volume optimization that resulted in enhanced productivity (Al-Ali et al 2015; Rahim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the encapsulated oxidizers released slowly from the polymer blend. The mechanism behind the diffusion-controlled release is comprised of i) the penetration of aqueous medium into the polymer matrix, ii) dissolution of the breaker, and iii) diffusion of the breaker into the aqueous medium caused by the difference in the concentration gradient (Satya Gupta and Cooney 1992; Aminabhavi et al 1996;Gulbis et al 1992). The desired release rate can be achieved by choosing the appropriate composition of polymer blend and breaker loading.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies over the last decade have identified fluid degradation and clean up as the most serious weakness of the guar-based fracturing fluids. 4 As a result, the industry has focused on improving the controlled degradation of the fluids with various polymer (gel) breakers [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%